Новые находки глубоководных нематод семейства Benthimermithidae в Южной Атлантике с описанием нового вида - Чесунов, А.В. (Вестник зоологии, 1988)
Two species of parasitic nematode genus Bentliimermis (В. arnaudi, В. marionensis), found in free living state, аге redescribed, and оnе is described as new. В. rosaliae sp. n.
is similar to В. leptosoma and В. arnaudi, differing from the first in thicker body (iпdex а 50 versus 81), presence of preamphidial setae, narrow amphidial саnаl, somewhat longer tail; from the second - in acute distal eпds of spiculae, other supplement shape, somewhat longer tail of particular shape.